2007
DOI: 10.1111/j.1443-1661.2007.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Choledochoscopy: Chromoendocholedochoscopy, Autofluorescence Imaging, or Narrow‐band Imaging

Abstract: Past and present results concerning assessment of choledochoscopy using chromoendoscopy, autofluorescence imaging (AFI), or narrow-band imaging (NBI) are summarized herein. On chromoendocholedochoscopy using methylene blue, cancer was stained dark blue. Interestingly, normal bile duct had dimple signs that are a significant feature of non-neoplastic mucosa. First-generation AFI (laser-induced fluorescence endoscopy-gastrointestine system) and system of autofluorescence endoscopy made it possible to detect neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Hoffman et al reported that with POCS, a neoplastic mucosa was depicted as an irregular mucosa with inhomogeneous staining, whereas a non-neoplastic mucosa without inflammation was shown as having a weak and homogenous staining, and an inflamed mucosa as having a dark-blue staining pattern [17]. We reported our initial experience with video PTCS (ECN-1530, 5-mm outer diameter and 2-mm working channel; Pentax Co., Ltd.) using methylene blue [16].…”
Section: Carbon Dioxide Insufflationmentioning
confidence: 94%
See 4 more Smart Citations
“…Hoffman et al reported that with POCS, a neoplastic mucosa was depicted as an irregular mucosa with inhomogeneous staining, whereas a non-neoplastic mucosa without inflammation was shown as having a weak and homogenous staining, and an inflamed mucosa as having a dark-blue staining pattern [17]. We reported our initial experience with video PTCS (ECN-1530, 5-mm outer diameter and 2-mm working channel; Pentax Co., Ltd.) using methylene blue [16].…”
Section: Carbon Dioxide Insufflationmentioning
confidence: 94%
“…It is possible to apply the currently available AFI system (CV-260SL/CV-290 processor, CVL-260SL/CVL-290SL light source; Olympus) to the aforementioned videocholangioscope [16]. AFI is a novel imaging technology in which endogenous fluorophores in the tissues are stimulated when the mucosa is illuminated by a short-wavelength light and a fluorescent light of a longer wavelength.…”
Section: Autofluorescence Imagingmentioning
confidence: 99%
See 3 more Smart Citations